2016
DOI: 10.1007/s10620-016-4238-7
|View full text |Cite
|
Sign up to set email alerts
|

Structural Change in Microbiota by a Probiotic Cocktail Enhances the Gut Barrier and Reduces Cancer via TLR2 Signaling in a Rat Model of Colon Cancer

Abstract: Administration of LBB modulates the gut microbiota and reduces colon cancer development by decreasing tumor incidence, multiplicity/count, and volume via enhanced TLR2-improved gut mucosa epithelial barrier integrity and suppression of apoptosis and inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
85
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(97 citation statements)
references
References 74 publications
3
85
1
Order By: Relevance
“…That finding suggested that constitutive luminal factors, such as microbial flora, were more important in the regulation of TLR expression than tumor‐related factors. Based on our present finding of a correlation between serum TLR2 levels and TLR2 expression in normal colorectal mucosa, combined with recent evidence that probiotic flora administration could induce TLR2 expression and downregulate inflammation in colon mucosa, we speculate that, in a subset of patients, it might be possible to downregulate systemic inflammation in CRC by modifying the luminal flora .…”
Section: Discussionsupporting
confidence: 69%
“…That finding suggested that constitutive luminal factors, such as microbial flora, were more important in the regulation of TLR expression than tumor‐related factors. Based on our present finding of a correlation between serum TLR2 levels and TLR2 expression in normal colorectal mucosa, combined with recent evidence that probiotic flora administration could induce TLR2 expression and downregulate inflammation in colon mucosa, we speculate that, in a subset of patients, it might be possible to downregulate systemic inflammation in CRC by modifying the luminal flora .…”
Section: Discussionsupporting
confidence: 69%
“…| 5615 enhancement induced by DAMPs released from chemical drug-treated tumor cells (Fang et al, 2014). It has also been reported that the anticancer effect of a probiotic cocktail is mediate by increasing TLR2 signaling in a rat model of colon cancer (Kuugbee et al, 2016).…”
Section: Tlr2/4mentioning
confidence: 97%
“…On the contrary, inflammatory biomarkers and side effects of chemotherapy were reduced in these patients (Golkhalkhali et al, 2018;Kotzampassi et al, 2015;Krebs, 2016;Z. Liu et al, 2015;Mego et al, 2015; reducing colitis, (l) increasing apoptosis, (m) increasing tumor suppressor miRNAs and, (n) increasing CXCR2 signaling (Agah et al, 2018;Arthur et al, 2013;Asha & Gayathri, 2012;Donohoe et al, 2014;Gamallat et al, 2016;Kahouli, Malhotra, Westfall, Alaoui-Jamali, & Prakash, 2017;Klewicka, Nowak, Zduńczyk, Cukrowska, & Błasiak, 2012;Kuugbee et al, 2016;Mendes et al, 2018;Mi et al, 2017;Mohania, Kansal, Kruzliak, & Kumari, 2014;Song et al, 2018;Talero et al, 2015;Walia, Kamal, Dhawan, & Kanwar, 2018;Zhang et al, 2015). studies include: intestinal microflora normalization, improvement of the gastrointestinal barrier, reduction of tumor formation, proliferation and growth of CRC cells and metastasis, reduction inflammatory responses, bacterial infection before and after colon cancer surgery.…”
Section: Human Studiesmentioning
confidence: 99%